HomeProxy: Exploring a Physical Proxy for Video Communication in the Home - Tang, John; Xiao, Robert; Hoff, Aaron; Venolia, Gina; Roseway, Asta; Therien, Patrick (ACM Conference on Human Computer Interaction (CHI 2013), 2013)
HomeProxy is a research prototype that explores supporting video communication in the home among distributed family members through a physical proxy. It leverages a physical artifact dedicated to representing remote family members to make it easier to share activities with them. HomeProxy combines a form factor designed for the home environment with a “no-touch” user experience and an interface that responsively transitions between recorded and live video messages. We designed and implemented a prototype and conducted a pilot study with eight pairs of users. Our study demonstrated the challenges of a no-touch interface and the promise of offering quick video messaging in the home.